Mystical Doctrines of Deification
1 online resource (204 pages)
Keywords: The notion of the deification of the human person (theosis, theopoièsis, deificatio) was one of the most fundamental themes of Christian theology in its first centuries, especially in the Greek world. It is often assumed that this theme was exclusively developed in Eastern theology after the patristic period, and thus its presence in the theology of the Latin West is generally overlooked. The aim of this collection is to explore some Patristic articulations of the doctrine in both the East and West, but also to highlight its enduring presence in the Western tradition and its relevance for contemporary thought. The collection thus brings together a number of capita selecta that focus on the development of theosis through the ages until the Early Modern Period. It is unique, not only in emphasising the role of theosis in the West, but also in bringing to the fore a number of little-known authors and texts, and analysing their theology from a variety of fresh perspectives. Thus, mystical theology in the West is shown to have profound connections with similar concerns in the East and with the common patristic sources. By tying these traditions together, this volume brings new insight to one of mysticism’s key concerns. As such, it will be of significant interest to scholars of religious studies, mysticism, theology and the history of religion.